Zinc-Air Battery – Powering Electric Vehicles to Smart Active Labels - Raihan Othman; Hens Saputra (University of Bandar Lampung (UBL), 2013)
The present paper reviews the development of zinc-air battery. Due to its high energy density advantage, the electrochemical system has been extensively studied and developed. However, major problems associated with the electrochemical system remain a formidable challenge, the utmost being to develop an electrically rechargeable zinc-air battery. Efforts made to overcome or mitigate the limitations concerned can be conceptually classified either as solving problems or seeking solutions. The changing paradigm from the electrically rechargeable system to the mechanically rechargeable system is illustrated as an example. Emerging innovations in smart active labels - flat, flexible and functional devices, particularly in healthcare industry, instigated the authors to develop zinc-air battery as a prospective micro-power source for smart active labels. The thin battery technology developed, in collaboration between IIUM and BPPT, is of low cost, comprises of green electro active materials, and able to operate in quasi-neutral electrolyte. These features fulfil the criteria for the battery to be incorporated into disposable smart active labels.